The structure and photoluminescence of a ZnO phosphor synthesized by the sol gel method under praseodymium doping. Issue 9 (18th February 2019) - Rhouma, F. I. H.; Belkhiria, F.; Bouzaiene, E.; Daoudi, M.; Taibi, K.; Dhahri, J.; Chtourou, R.
Abstract : This work outlines some interesting results regarding the effects of Pr 3+ substitution on the structural and optical properties of ( x = 0 and 0.02) samples. Abstract : This work outlines some interesting results regarding the effects of Pr 3+ substitution on the structural and optical properties of ( x = 0 and 0.02) samples. Our samples were synthesized using the Pechini sol–gel method. The structural study using Rietveld refinement of XRD patterns showed a hexagonal structure with the P 63 mc space group for all the samples and also the existence of a secondary phase attributed to the praseodymium oxide (Pr6 O11 ) for 2% wt Pr-doped ZnO. The refinement results revealed that both the lattice parameter and the unit cell volume increase with the increase of Pr content. X-ray peak broadening analysis was used to evaluate the crystallite size and lattice strain by the Williamson–Hall (W–H) method and size–strain plot method (SSPM). The physical parameters such as strain, stress and energy density values were also calculated using the W–H method with different models, namely uniform deformation model (UDM), uniform stress deformation model (USDM) and uniform deformation energy model (UDEDM). The obtained results showed that the mean particle size of the ZnO and Pr0.01 Zn0.97 O estimated from W–H analysis and the SSPM method are highly intercorrelated. Shifting of the absorption edge to lower wavelength and blue shift of the band gap are observed in the UV-visible spectra of Pr-doped ZnO samples. Particular emphasis was put on the PL measurements of such composites. A noticeable decrease of the maximum intensity of PL response was found after adding Pr 3+ to ZnO. This finding is discussed in terms of the photo excited limitation of electron–hole pairs in such nanocomposites.